Induction of fertile estrus during lactation in sows - Jeffrey S Stevenson; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1983)
Our objective was to determine the effectiveness of inducing estrus during lactation by reducing the nursing load of the sow between 2 and 4 weeks after farrowing. lactating sows were separated from their litters for either 6 (20 sows) or 12 (10 sows) hr/day between 2 and 4 weeks postpartum. For comparison, the litters of other sows were weaned at either 2 (13 sows) or 4 (16 sows) weeks of age. Estrus was induced in 13 of 20 (65%) sows and 5 of 10 (50%) sows that were separated from their litters for 6 or 12 hr/day during lactation, respectively, compared with 0/13 and 0/16 sows weaned at 2 or 4 weeks. The 18 sows that showed estrus during lactation averaged 5.9 days from the first day of litter separation to estrus compared with 4.4 and 4.2 days from weaning to estrus for sows weaned at 2 or 4 weeks. Fertility traits (number of corpora lutea, eggs fertilized, fertilization rate, eggs cleaved, and cleavage rate) were unaffected by treatment. Daily separation of sows from their litters for at. least 6 hr/day resulted in 60% of the sows showing synchronous estrus in 4 to 8 days with fertility similar to that of sows weaned completely at 2 or 4 weeks postpartum.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Fertile; Estrous; Lactation